Monte carlo simulation of epitaxial growth of gainassb films (2014)
Material engineering finds an important support on simulation methods. The study of semiconductors growth techniques through simulation allows the determination of the influence of some growth parameters on the film properties. Experimentally, the variations of these parameters are difficult due to the high experimental demands and expenses. In this work we present the numerical simulation of the epitaxial growth of GaInAsSb by three methods. Devices based on this semiconductor material are thermophotovoltaic generators. The solid-on-solid approximation was used, considering the unit cell formed by the four constituent elements, in the establish proportions according to the choose stoichiometry. Through the Kinetic Monte Carlo method we obtained a high coincidence between the simulated film morphology and the obtained in the experimentally grown films.